Teaching Human Rights from Below: Towards Solidarity, Resistance and Social Justice - Canlas, Melissa; Argenal, Amy; Bajaj, Monisha (Radical Teacher, 2015)
In this article, we discuss our approaches, pedagogies, and practices for a weekly human rights club that serves immigrant and refugee youth. The research team is involved in a research collaboration with a public high school in a large urban area on the West Coast. In this article, we discuss some of our curricular and pedagogical strategies and students’ responses to lesson plans and activities that aimed to build solidarity, resistance to dominant and assimilative narratives, and action towards social justice. Our approach focuses on intersecting a transforamtive human rights perspective with the praxes of critical pedagogies and social justice. This article discusses a radical approach to teaching Human Rights along three key themes: student-centered human rights pedagogy, cultural wealth and HRE, and students’ articulation of human rights language into action.